Effectiveness of Value Clarification Technique (VCT) in Learning History to Increase the Value Nationalism, Democracy, and Multiculturalism - I Kadek Yudiana (BIRCU, 2020)
Leaving the XX century and entering the XXI century, the development of society was marked by the emergence of a new form of society, the information society The objective conditions faced by the Indonesian people today are severe conditions that can be seen in various dimensions of the problem, from the limited issue of public guarantees, low human quality, conflicts and violence that have emerged, to the government's low credibility.The spirit of nationalism or nationalism must be nurtured and developed to be relevant to today's challenges. Related to the concept of nationalism, Democracy education needs to be implemented because the nation's democratization process is very dependent on education. A democratic state of education constraints choice among good lives not only out of necessity but out of concern for civic virtue. Multicultural education is in line with the development of democracy. For Indonesia which is multi-ethnic, education that enhances multicultural spirit is an urgent need. Learning history has important relevance related to the formation of national character. Based on learning style tests, students are grouped in the categories of visual students and auditory students. For the experimental class the visual students were 42 people, and the auditory students were 45 people. In the control class, there were 26 visual students, and 21 auditory students. Based on data from previous research results obtained ¬ score learning outcomes for the visual experimental class and auditory experimental class. where for the visual experimental class the average value of the posttest and pretest was 151.12 and 140.56, while for the average posttest and pretest the auditory experimental group was 151.89 and 140.18. person.